2019
DOI: 10.3390/f10020130
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of microRNAs in the SAM and Leaves of Populus tomentosa

Abstract: The shoot apical meristem (SAM) is a crucial tissue located at the tops of plants which can continually grow and differentiate to develop into all aboveground parts. SAM development is controlled by a series of complicated molecular regulation networks, among which microRNAs (miRNAs) and their target genes play key roles. However, little is known about these miRNAs in woody plants. In this study, we used small RNA (sRNA) sequencing to build four libraries derived from shoot tips and mature leaf tissues of Popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Particularly, an integrated metabolomic and transcriptomic analysis can provide comprehensive information on the molecular regulatory networks involved in the response to heat stress. Populus tomentosa, an economically important tree species, is widely distributed in China [20]. It is fast growing and highly resistant to environmental stresses, especially to high temperature stress.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, an integrated metabolomic and transcriptomic analysis can provide comprehensive information on the molecular regulatory networks involved in the response to heat stress. Populus tomentosa, an economically important tree species, is widely distributed in China [20]. It is fast growing and highly resistant to environmental stresses, especially to high temperature stress.…”
Section: Introductionmentioning
confidence: 99%
“…[44], Gossypium hirsutum L. [45], and Camellia sinensis (L.) O. Kuntze [46], major peaks at 24-nt were also seen in sRNA length distribution patterns. Other studies, in different plants, identified 21-nt sRNAs as the most abundant class [47,48]. Additionally, differences in distribution patterns have also been observed in different lines of the same plant [49] and different developmental stages [50].…”
Section: Mirna Population Identified In Pecanmentioning
confidence: 88%
“…These TFs are also promoted by the up-regulated activities of targeted SPLs genes and further coordinate actions of flowermaking genes, and finally, cause suppression of the FT gene involved in the floral development process in poplar (see. Table 1) [19].…”
Section: The Mir156 Master Regulator To Synchronize Complex Biologicmentioning
confidence: 99%
“…Since, plant miRNAs are implicated in virtually all biological functions in plants especially, to control growth and development under adverse environmental conditions [14]. Recently hundreds of miRNAs families have been identified in various crop plants [19][20][21] that deposited in various microRNAs repositories [22,23]. These databases provide a great wealth of knowledge related to miRNAs, and their biogenesis, structures, functions, and evolutionary origins.…”
Section: Introductionmentioning
confidence: 99%